The Role of Entrepreneurship Education in Developing Students Entrepreneurial Intentions Through Self-Efficacy - Damayanti Damayanti; Acep Fatchuroji; Andi Indra Saputra Alamsyah; Wahyu Muh Syata (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study explores the role of entrepreneurship education in shaping students' entrepreneurial intentions through the development of self-efficacy. Entrepreneurship education serves as a bridge between the academic environment and the professional world, while self-efficacy acts as a psychological factor that influences individuals’ motivation to pursue entrepreneurial paths. This study employed an integrative literature review supported by bibliometric analysis to synthesize previous empirical findings on entrepreneurship education, self-efficacy, and entrepreneurial intention.. Relevant journal articles were systematically identified through academic databases such as Google Scholar and Scopus, focusing on studies published in the past five years that examine the relationship between entrepreneurship education, self-efficacy, and entrepreneurial intention. The review process included stages of topic refinement, keyword-based search, selection based on inclusion criteria, and thematic analysis. The findings indicate that self-efficacy is closely associated with students’ entrepreneurial intentions through five key dimensions: (1) belief in one’s ability to design and manage a business, (2) readiness to face challenges and take initiative, (3) alignment with or resistance to prevailing social norms related to entrepreneurship, (4) resilience in overcoming obstacles, and (5) confidence in making entrepreneurial decisions. These findings suggest that entrepreneurship education, when combined with self-efficacy development, can foster stronger interest and preparedness among students to engage in entrepreneurial endeavors. The study underscores the importance of designing entrepreneurship programs that integrate both cognitive and psychological dimensions to promote entrepreneurial readiness.